NAVIGATING THE COMPLEX WORLD OF FOOD AND BEVERAGE MANAGEMENT IN HOTELS: CHALLENGES, OPPORTUNITIES, AND BEST PRACTICES - Zrnić, Miloš; Gajić, Tamara; Vukolić, Dragan; Knežević, Snežana; Knežević, Miroslav (The Business of Tourism, 2023)
This paper explores various aspects of food and beverage management in hotels and highlights the significant role this area plays in hotel operations. This paper reviews the literature published since 2013, focusing on the application of the latest approaches in food and beverage management hotels in general. A comparative analysis was used to gain a better insight into food and beverage management in different hotels. The paper will analyze key trends in the field of food and beverage management in hotels and investigate how the application of new technologies and approaches can affect the efficiency and profitability of business.